2018
DOI: 10.3390/w10040511
|View full text |Cite
|
Sign up to set email alerts
|

Corn Straw as a Solid Carbon Source for the Treatment of Agricultural Drainage Water in Horizontal Subsurface Flow Constructed Wetlands

Abstract: Agricultural drainage water with a low C/N ratio restricts the nitrogen and phosphorus removal efficiencies of constructed wetlands. Thus, there is a need to add external carbon sources to drive the nitrogen and phosphorus removal. In this study, the effects of the addition of corn straw pretreated with different methods (acid treatment, alkali treatment, and comminution) on treating agricultural drainage water with a low C/N ratio were investigated in constructed wetlands. The results showed that soaking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Therefore, the results from the current study provided confidence that the reeds straw addition could be a good strategy and technical solution for low C/N wastewater treatment, by a considerable enhancement of TN and TP removal of 59.7% and 35.0%, respectively, at HRT of four days. Although it was questionable to compare this enhancement with other cases of different materials being added and the varied operation condition, as well as different CW system configuration, the enhancement was comparable from the limited literature, 37.2% for TN and 30.5% for TP [ 12 ]. Chen et al [ 11 ] had concluded that denitrification contributed to 54–94% N removal in CWs.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…Therefore, the results from the current study provided confidence that the reeds straw addition could be a good strategy and technical solution for low C/N wastewater treatment, by a considerable enhancement of TN and TP removal of 59.7% and 35.0%, respectively, at HRT of four days. Although it was questionable to compare this enhancement with other cases of different materials being added and the varied operation condition, as well as different CW system configuration, the enhancement was comparable from the limited literature, 37.2% for TN and 30.5% for TP [ 12 ]. Chen et al [ 11 ] had concluded that denitrification contributed to 54–94% N removal in CWs.…”
Section: Resultssupporting
confidence: 54%
“…The reeds straw were prepared from the harvested mature reeds in the Erhai riparian natural wetland. After exposure outside to dry, the reeds were chopped into 1~2 cm bars and then mixed with the soil [ 12 ]. The total mass of the reed bars was about 9.2 kg with a specific filling quantity of 19.2 kg/m 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Horizontal or vertical subsurface-flow constructed wetlands can be an advantage in relation to SFCWs in regards to smaller area requirements. Li et al [112] demonstrated that five newly constructed experimental horizontal-flow wetlands effectively retained P from agricultural drainage discharge (35%, 38%, 38%, 57% and 31%), which was likely owing to the unsaturated medium with P. The study also demonstrated that the percentage P retention increased after the addition of a carbon source, which probably favored microbial uptake of P, and under longer HRTs. The use of subsurface-flow constructed wetlands, however, is largely restricted to the treatment of wastewater (e.g., sewage) and is less used in agricultural catchments than SFCWs due to high maintenance costs, risk of clogging and limited P sorption capacity of the medium [113].…”
Section: Countrymentioning
confidence: 90%